Parallel array histogram architecture for embedded implementations. Issue 2 (1st January 2013) - Gan, Q.; Langlois, J.M.P.; Savaria, Y.
Abstract : Proposed is a parallel array histogram architecture (PAHA) suitable for embedded implementations. The PAHA uses a register array instead of a memory block to store the histogram bins. In each step, M inputs can be processed in parallel to update the histogram bins without any additional latency. Also described is a second version of the PAHA with a flexible number of inputs, potentially avoiding the need for multiple PAHAs in a single application. Implementation results show that the architecture can achieve a super‐linear speed‐up of 43.75× for a 16‐way PAHA when compared to a software implementation in a general‐purpose processor.